2013
DOI: 10.1016/j.healthpol.2013.03.018
|View full text |Cite
|
Sign up to set email alerts
|

Support for a smoke-free bylaw in parks and on beaches

Abstract: These findings suggest strong public support in Vancouver for the smoke-free bylaw in parks and on beaches. Jurisdictions considering such legislation should address attitudes which can promote or hinder its adoption. Examination of such policy support on diverse groups within the population may enhance the development of equitable public health policy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(12 citation statements)
references
References 22 publications
0
11
0
1
Order By: Relevance
“…Moreover, once bans are implemented, support for restrictions also increases among current smokers [ 10 , 11 , 12 ]. Although a greater proportion of non-smokers support indoor and outdoor smoking bans [ 10 , 13 , 14 , 15 ], some recent evidence indicates that the majority of smokers support indoor bans [ 16 ]. Moreover, support for smoke-free laws is positively associated with quit attempts [ 17 ].…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, once bans are implemented, support for restrictions also increases among current smokers [ 10 , 11 , 12 ]. Although a greater proportion of non-smokers support indoor and outdoor smoking bans [ 10 , 13 , 14 , 15 ], some recent evidence indicates that the majority of smokers support indoor bans [ 16 ]. Moreover, support for smoke-free laws is positively associated with quit attempts [ 17 ].…”
Section: Introductionmentioning
confidence: 99%
“…For example, a recent Canadian study found very strong parental and caregiver support for smoke-free polices in playgrounds to reduce potential health risks associated with SHS exposure among children [13]. However, our park user telephone survey suggested that park users in Vancouver differed regarding support for the bylaw by smoking status, gender, ethno-cultural affiliation, education, and marital status [43]. That is, smokers were less supportive of the bylaw; women were significantly more likely to support the bylaw; individuals from various visible minority groups were significantly more likely to support the law than those of White or European Ancestry; and those with a university degree were significantly more likely to support the law as compared to those with a high school degree or lower.…”
Section: Discussionmentioning
confidence: 91%
“…Beliefs regarding the bylaw were that it would: improve the health of people in the city (total = 82 %, nonsmokers= 86 % vs. smokers = 43 %); protect the health of non-smokers, including children who visit parks and beaches (total = 83 %, nonsmokers = 86 % vs. smokers = 56 %); encourage people to quit smoking (Total = 49 %, nonsmokers = 52 % vs. smokers = 22 %); discourage youth from starting smoking (Total = 49 %, nonsmokers = 50 % vs. smokers = 33 %), infringe on the right of smokers (total = 42 %, nonsmokers = 39 % vs. smokers = 71 %); and protect people from exposure to secondhand smoke (total = 84 %, nonsmokers = 88 % vs. smokers = 52 %) [43]. Women were significantly more likely than men to believe that the bylaw would protect the health of nonsmokers (including children) who visit parks and beaches (64.1 % vs. 35.9 %) and protect people from exposure to secondhand smoke (63.6 % vs. 36.4 %).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations